Alpines, trees, and refugia in Europe - Birks, H; Willis, K (Taylor and Francis, 2008)
Refugia were critically important for species survival in both glacial and interglacial stages of the Quaternary. The classical view of glacial stages is that alpine and arctic plants were widespread in the lowlands of central Europe and around the margins of the continental and alpine ice-sheets, whereas trees were restricted to localised refugial areas in southern Europe and the Mediterranean basin. New palaeobotanical evidence in Europe suggests, however, that this classical view is incomplete and that tree distributional ranges during the glacial stages were more extensive and included many more local areas of small populations in central and eastern Europe growing in so-called 'cryptic' refugia. We argue that this concept of 'cryptic' refugia is also applicable to arctic and alpine plants during temperate interglacial stages where small localised populations grow in naturally open habitats that are not beyond or above the forest limit. Determination of the whereabouts of these cold- and warm-stage 'cryptic' refugia is very important in our understanding of the spatial patterns of present day genetic diversity and the possible rates of spread of trees in response to future climate change.